PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CORPORATE GOVERNANCE, DAN PROFITABILITAS TERHADAP KUALITAS PELAPORAN KEUANGAN (Studi Empiris pada Perusahaan Sektor Energi dan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2020) - Bima Adhitya Nugroho; Darsono Darsono (Diponegoro Journal of Accounting, 2023)
This study aims to find empirical evidence regarding to the effect of corporate social responsibility disclosure, institutional ownership structure, profitability, audit quality, and audit committee independence on the quality of financial reporting proxied by value relevance, so that it can have implications for investors to find out relevant accounting information and transparency in financial reports.The data are collected by documentation method. The research sample is energy and mining sector companies that listed on the Indonesia Stock Exchange in 2018-2020. The number of samples that meet the requirements and after eliminating outlier data in this study is 151 firm-years. The data analysis technique used is multiple linear regression.The results showed that the disclosure of corporate social responsibility and institutional ownership structure have a positive effect on the quality of financial reporting, while profitability, audit quality, and audit committee independence have no effect.